Infecção natural por Histomonas meleagridis em pavões-indianos (Pavo cristatus) - da Costa, Ricardo Almeida; Pereira, Ana Paula Maurique; Silveira, Caroline da Silva; Anjos, Bruno Leite (Acta Scientiae Veterinariae, 2018)
Background: Histomonas, also known as blackhead, is a protozoan disease caused by Histomonas meleagridis (phylum Parabasalia, class Tritrichomonadea, order Tritrichomonadida, family Dientamoebidae/Protrichomonadinae) and, characterized by enteric and hepatic lesions in several species of domestic and wild gallinaceous. Among the most affected species, turkeys are those with greater morbidity and mortality. Blackhead is the second most important disease caused by protozoa in domestic poultry, affecting especially young birds and causing severe economic losses, with decrease in production, lack of uniformity of lots and costs with treatment and control. Its occurrence must be monitored, especially in large poultry exporting countries, such as Brazil. The aim of this study is to report an outbreak of histomoniasis in Indian peacocks Case: A peacocks group created together with chickens showed clinical signs characterized by apathy, head down and bruised head, eyes closed, anorexia, yellow or pale stools and death. At necropsy, the cecum showed intense thickening of the wall with irregularity in the serous layer and abundant deposit of friable material, amorphous, yellowish color with areas reddish in the lumen with large number of filiform white parasites from 1 to 1.5 cm in length, morphologically compatible with Heterakis gallinarum. The liver showed large and circular, multifocal, whitish areas that extended towards the parenchyma. Histologically, was observed marked transmural typhlitis, severe proliferation of fibroblasts with multifocal neovascularization, histiocytic infiltrate, giant cell enlargement, bacterial myriads, presence of eosinophilic circulars trophozoites, with 6-20 μm in diameter, morphologically compatible with Histomonas meleagridis. These structures were positive in PAS staining. In the liver, a lesion was characterized by aleatory necrotizing hepatitis with abundant macrophagic and heterophilic infiltrate and some lymphocytes, as well as several foci of necrosis associated with numerous parasitis, intralesional, weakly eosinophilic, PAS-positive structures similar to those observed cecum. Discussion: All aspects observed in this outbreak were characteristic of Histomonas meleagridis infection. This protozoal infection occurs predominantly in turkeys, with high rates of morbidity and mortality, however, can affect chickens, chukar partridges, pheasants and peacocks. Histomoniasis occurs after ingestion of nematode eggs present in the feces of birds and earthworms. In addition, to the intestine and liver, there may be systemic parasitism with lesions in other organs such as kidneys, lungs, spleen and cloacal sac. Overcrowding of animals, the creation and use of chickens to hatch peacocks eggs, as well as the poor hygiene conditions were the main risk factors for the development of the disease. Due to the absence of specific clinical signs, the disease can be easily confused with other disorders. macroscopic and microscopic examinations are recommended to assist in confirming the definitive diagnosis of histomoniasis. Thus, it can be said that H. meleagridis may be cause of mortality in peacocks (Pavo cristatus) created in free system in Rio Grande do Sul, State. The diagnosis of this condition should be considered in cases of mortality in exotic bird breeding, especially when created together with most resistant species such as chickens and other poultry.